(untitled) (Journal of Hama University, 2022)
The study was conducted on the strawberry plant (Oso Grande) at the Faculty of Agriculture - Damascus University- with the aim of studying the effect of foliar spraying with different concentrations of humic acid (0, 0.5, 1, and 2) ml/liter on growth and productivity of strawberry. The results showed that foliar spraying with humic acid improved all studied indicators, as the application of treatment (2) ml/l increased vegetative growth indicators (plant height, crown diameter, number of crowns, number of purlins, number of leaves, leaf area) and indicators of Productive growth (number of flowers, number of fruits, percentage of fruit set, fruit weight, plant yield) in addition to an increase in the TSS, and Vitamin C concentration to 5.4% and 47.33 mg/100g fresh weight respectively while the TA content of fruits decreased with the increase in the concentration of humic acid In the mean to 0.76% compared to the control 0.42%.